Benefits of enterprise resource planning. - Kwan, Cailyn. (2008)
In light of the growing talk on Enterprise Resource Planning(ERP), this research has been conducted to investigate the benefits sought by companies implementing ERP, the extent to which these benefits were achieved and the benefits that contributed to user satisfaction in Singapore.